Prospects for using entomopathogenic nematodes as a biocontrol agent against fungus gnats, bradysia spp. (Diptera: Sciaridae) in nursery and glass house crops - Katumanyane, Agil (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScConsEcol)--Stellenbosch University, 2017.